THE ROLE OF SATELLITE CHANNELS IN PROMOTING CITIZENSHIP VALUES AMONG STUDENTS AT THI- QAR UNIVERSITY (American Journal of Research in Humanities and Social Sciences, 2024)
The current descriptive study aims to identify the role of Iraqi satellite channels in promoting citizenship values among students at Thi Qar University. The study sample consisted of 500 students from various humanities and scientific colleges to design and build a citizenship values scale, 100 students for the application sample, and 10 students for the exploratory experiment who were selected by the researcher in the second semester of the 2023/2024 academic year. The discriminatory power of the items was used to detect strong items and weak items, as well as the internal consistency of the items to determine the relationship of the item to the total score of the scale. The researcher used split-half and Cronbach's alpha to detect the stability of the scale. The results showed that the Iraqi satellite channels watched by university students do not contribute to enhancing the values of citizenship. Based on the results of the current study, a set of recommendations were proposed by the researcher at the end of the study.